2018
DOI: 10.1155/2018/8620150
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Analysis of the Anterior Capsulotomy Edge: A Comparative Study between Femtosecond Laser-Assisted Capsulotomy and Manual Capsulorhexis

Abstract: Purpose To compare the capsule edges ultrastructure obtained by two femtosecond laser-assisted cataract surgery (FLACS) platforms and manual continuous curvilinear capsulorhexis (CCC) using scanning electron microscopy (SEM). Setting Eye Clinic, University of Trieste, Italy. Design Experimental comparative study. Methods 150 anterior capsules were collected and divided into three groups as follows: Group 1 (50 capsules) obtained with manual CCC, Groups 2 and 3 (each with 50 capsules) obtained with the Catalys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In comparison to other platforms, the Catalys™ Precision Laser System has been reported as a robust laser system, demonstrating superiority in complete capsulotomy when compared to the LenSx laser platform. 19 , 20 , 21 , 22 Conrad-Hengerer et al, evaluated the use of femtosecond laser–assisted capsulotomy in eyes with intumescent cataract using the Catalys™ Precision Laser System and concluded that FLACS was safe to avoid intraoperative capsule complications related to increased intracapsular pressure. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other platforms, the Catalys™ Precision Laser System has been reported as a robust laser system, demonstrating superiority in complete capsulotomy when compared to the LenSx laser platform. 19 , 20 , 21 , 22 Conrad-Hengerer et al, evaluated the use of femtosecond laser–assisted capsulotomy in eyes with intumescent cataract using the Catalys™ Precision Laser System and concluded that FLACS was safe to avoid intraoperative capsule complications related to increased intracapsular pressure. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies could already demonstrate analysis of femtosecond laser-assisted capsulotomy versus manual capsulorhexis 4 , 13 16 . Tognetto et al found a similar irregularity level with the Catalys Laser system (1.4 ± 0.63) as we did for Group 1 with the Ziemer Z8 system when performing with the capsulorhexis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Some studies have shown a better ability to maintain centration and circularity with femtosecond laser systems, but at the cost of a more ragged edge from the laser pulses. 9 Others have indicated that automated capsulotomy with femtosecond laser systems may be helpful in complicated cases such as white cataracts. 10 Frequent concerns related to the use of femtosecond laser systems are related to the cost of the device and the increased procedure time.…”
Section: Introductionmentioning
confidence: 99%